The Application of the Controllability Principle and Managers$1 (BResponsess A Role Theory Perspective - Fischer, Franz Michael; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
In recent works on the design of management control systems, interest in the controllability principle has seen a revival. Franz Michael Fischer investigates the effects of the principle$1 (Bs application on managers$1 (Bresponses. The author further explores the impact of several important contextual factors on the basic relationships and, thus, develops moderated mediation models. The results are based on interview data gathered from 12 managers and survey data from 432 managers which confirm most of the hypotheses. The data analysis reveals that the application of the controllability principle has a significant effect on role stress and role orientation which, in turn, are related to managerial performance and affective constructs.s
Literature Review on the Controllability Principle -- to Role Theory -- Development of the Causal Models -- Development of the Research Design -- Empirical Results -- Discussion -- Conclusion.
Keywords: Economics; Auditing; Economics/Management Science; Accounting/Auditing.